Alcohol, illicit drugs and health promotion in Ireland, 1945-1996 - Butler, Shane (Trinity College (Dublin, Ireland). School of Social Work and Social Policy, 2000)
Introduction: The health and social problems associated with the consumption of alcohol and of illict drugs have long been causes of concern in international public health circles. Empirical syudies (Bruun et al, 1975; Davies and Walsh, 1983; Edwards et al, 1994) have revealed that in the second half of this century alcohol consumption has increased in most Western societies, as have many indicators of alcohol-associated morbidity and mortality. Both national and international health authorities have sought during this period to devise treatment responses for those already experiencing problems and prevention strategies to reduce the incidence of drinking problems. Similarly, there has been a major expansion in the range of illict drugs widely available and widely used. This, to some extent, is a by-product of developments in the area of science and technology since drugs, like other commodoties, may now be transported easily and quickly around the world away from their geographical source, and synthetic drugs may equally easily be manufactured in relatively unsophisticated laboratories.
Keywords: Social Studies, Ph.D.; Ph.D. Trinity College Dublin